Predictors of Retention and Recidivism of Justice-Involved Women in a Community-Based Gender-Responsive CBT Program. (March 2022) - Zarling, Amie; Scheffert, Roxann; Russell, Dan
The purpose of this study was to evaluate pretreatment differences between program completers and noncompleters, as well as those who recidivated and those who did not, among a sample of 112 justice-involved women referred to a gender-responsive cognitive-behavioral program as part of supervision recommendations. Risk scores, adverse childhood experiences, emotion dysregulation, self-control, and various demographic variables were examined as predictors of program completion and 1-year recidivism. Results of logistic regression indicated that higher risk scores significantly predicted program noncompletion and 1-year recidivism, and noncompleters were 6 times more likely to recidivate than completers. These findings reveal characteristics of women as they relate to the likelihood of completing criminal justice treatment programs, and indicate a greater need for intensive support among high-risk women.